Utilizing head simulation training in dental school education: Time and cost implications (Journal of Applied Learning and Teaching, 2024)
Studies have suggested that the head simulator was a useful instrument for imparting hand skills for tooth removal in dental school. Although head simulator models are used by students to develop their dental hand skills, they have noteworthy limitations that restrict the breadth of knowledge and abilities that students can learn. The purpose of this current study was to determine cost and time as barriers to the effectiveness of head simulator use in dental schools. Regarding the perceived time requirements for dental courses, most participants (51.6%) disagreed that the use of head simulators extended the course duration. In terms of the availability and cost of head simulators, 40% of respondents found the availability to be above average or excellent, while 20% rated it below average or very poor. The current study suggests that the cost of head simulators did not affect the availability of the devices to oral health professionals during their school years. And the head simulator use did not extend the duration of the dental course.